1999
DOI: 10.1002/chin.199930316
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Influence of Curcumin Treatment on Collagen Metabolism in Experimental Myocardial Necrosis in Rats

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…[29][30][31] It has also shown that curcumin pre-and post-treatment exerts membrane stabilizing action by decreasing the degradation of collagen matrix by inhibiting the release of lysosomal enzymes. [32][33][34] In contradiction to this, there are in vitro studies which suggests curcumin's prooxidant potential. 16,17,35 However, data in support of its in vivo toxic effects remain unavailable.…”
Section: Discussionmentioning
confidence: 87%
“…[29][30][31] It has also shown that curcumin pre-and post-treatment exerts membrane stabilizing action by decreasing the degradation of collagen matrix by inhibiting the release of lysosomal enzymes. [32][33][34] In contradiction to this, there are in vitro studies which suggests curcumin's prooxidant potential. 16,17,35 However, data in support of its in vivo toxic effects remain unavailable.…”
Section: Discussionmentioning
confidence: 87%
“…The model is characterized by an extraordinary technical simplicity, an excellent reproducibility as well as an acceptable low mortality [6]. Myocardial infarction induced by ISO has been reported to show many metabolic and morphological aberrations in the heart tissue of the experimental animals similar to those observed in human myocardial infarction [7]. ISO induced necrosis is maximal in the subendocardial region of the left ventricle and in the intraventricular septum [8].…”
Section: Isoproterenol Induced Myocardial Infarctionmentioning
confidence: 99%
“…In isoproterenol‐induced myocardial necrosis models, curcumin has been reported to have significant effects on the prevention of collagen synthesis (Nirmala, Anand, & Puvanakrishnan, ). Moreover, histopathologic findings also showed that curcumin treatment decreased the degree of myocardial necrosis in isoproterenol‐treated rats (Nazam Ansari, Bhandari, & Pillai, ; Nirmala & Puvanakrishnan, ).…”
Section: Antioxidative and Anti‐inflammatory Properties Of Curcumin Imentioning
confidence: 99%